2020
DOI: 10.1136/bmjopen-2019-036086
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diabetes and pre-diabetes in Bangladesh: a systematic review and meta-analysis

Abstract: ObjectiveThe purpose of this paper is to perform a systematic review and meta-analysis in order to summarise the prevalence of diabetes and pre-diabetes and their associated risk factors in Bangladesh.DesignSystematic review and meta-analysis.ParticipantsGeneral population of Bangladesh.Data sourcesPubMed, Medline, Embase, Bangladesh Journals Online, Science Direct, Scopus, Cochrane Library and Web of Science were used to search for studies, published between 1st of January 1995 and 31st of August 2019, on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 46 publications
7
44
0
Order By: Relevance
“…The results showed that the pooled prevalence of diabetes based on 6 population-based cross-sectional studies was 12.13%, with a total sample of 7071 individuals. Compared with neighbouring countries sharing a similar lifestyle and culture, the pooled prevalence of diabetes in Afghanistan is higher than in Bangladesh (7.8%) [ 25 ] and Nepal (8.4%) [ 26 ], while lower than in Pakistan (14.7%) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the pooled prevalence of diabetes based on 6 population-based cross-sectional studies was 12.13%, with a total sample of 7071 individuals. Compared with neighbouring countries sharing a similar lifestyle and culture, the pooled prevalence of diabetes in Afghanistan is higher than in Bangladesh (7.8%) [ 25 ] and Nepal (8.4%) [ 26 ], while lower than in Pakistan (14.7%) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes has been the second most common comorbidity (9.7%) among COVID-19 patients after cardio-metabolic disorders (12.5%) [1,3]. In 2019, the International Diabetes Federation (IDF) reported that 465 million (9.3%) people in the world were diagnosed with diabetes, and by 2045 the figure is predicted to grow to 700 million [4]. About 79% of people with diabetes live in low-income or middle-income countries, with more than 60% living in Asian countries [5].…”
Section: Introductionmentioning
confidence: 99%
“…About 79% of people with diabetes live in low-income or middle-income countries, with more than 60% living in Asian countries [5]. In Bangladesh, there were 7.1 million people suffering with diabetes in 2015, with 3.7 million undiagnosed cases and nearly 129,000 deaths [4,6]. Other reports suggest that there are around 10 million diabetic patients in Bangladesh [7] with almost one in ten adults living with diabetes [8].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis conducted by Saquib et al reported the pooled hypertension and type 2 diabetes prevalences as 13.7% (12.1-15.3%) and 6.7% (4.9-8.6%), respectively [5]. Another study by Akhter et al reported a pooled diabetes prevalence of 7.8% (95% CI: 6.4-9.3) for the general population [6].…”
Section: Introductionmentioning
confidence: 99%